The second order phase transition in Sn₂P₂S₆ crystals: anharmonic oscillator model - Yevych, R.M.; Vysochanskii, Yu.M. (Condensed Matter Physics, 2008)
Statistical theory for ferroelectrics based on triple well anharmonic potential was used for the case of structural
second order phase transition in Sn₂P₂S₆ crystals. Parameters of effective Hamiltonian of the model were
estimated using available experimental data. These findings confirm the assumption that the phase transition
in these crystals is located in crossover region between order-disorder and displacive type, and very closely
to tricritical point. Статистична теорiя для сеґнетоелектрикiв, що базується на трьохямному ангармонiчному потенцiалi, використана для випадку структурного фазового переходу другого роду в кристалах Sn₂P₂S₆. Параметри ефективного гамiльтонiану моделi оцiненi використовуючи наявнi експериментальнi данi. Встановлено, що фазовий перехiд в цих кристалах розташований в кроссовернiй областi мiж фазовими переходами типу “лад-безлад” та типу змiщення, а також близько до трикритичної точки.